ANALISIS KEDUDUKAN ANAK LAHIR DI LUAR NIKAH TANPA WALI NASAB DALAM PERSPEKTIF HUKUM KELUARGA ISLAM DI INDONESIA - Arasuli, Rosihah; Maotsiqon Azzam Ghiyatsulhaq; Putri Andini; Nadya Arafah Zahra; Dzakiyatul Qowiy Bathin (Prodi Hukum Keluarga Islam IAI Uluwiyah Mojokerto, 2026)
The study assessed the legal positions of children born without legal marriage and without a guardian nasab, from an islamic family's legal perspective in Indonesia. The study is set against the rising practice of siri marriage as well as the juridical effect on the child's position of a relationship that is not officially recognized by the state. Research methods used are descriptive with constitutional and conceptual approaches, and data collection through literature studies involving legislation, literacy, and judicial decisions. Studies have shown that according to islamic law, children born outside of marriage are only nasab related to mothers. However, in Indonesia's positive laws, as evidenced in ruling constitutional court number 46/ puu-viii /2010, the child can obtain legal recognition from his biological father if it is supported by a legitimate instrument of evidence. If the child has no guardian, then the role of guardian can be performed by the guardian of the judge according to the provision of islamic law to ensure the legitimacy of marriage. The study asserts that while the positions of an illegitimate child differ from the legal child, such rights as livelihood, education, and legal recognition remain protected by both islamic and national law.